Measuring the impacts of cooperative membership on household income: A case study of Zanzibar - Mbarouk J. Ali; Gao Qianqian; Ge Wenguang (South African Journal of Economic and Management Sciences, 2024)
Background: It is commonly acknowledged that cooperatives play important social functions that raise the standard of living for their members, particularly those who originate from rural, and low-income backgrounds.